FUNGSI TARI NADRAK PAGUYUBAN RUKUN SANTOSA DESA BRONGKOL KABUPATEN SEMARANG - Karinsa Krisna Murti; Slamet Slamet (Greget, 2021)
The article entitled Functions of the Nadrak Dance Association of Rukun Santosa, Brongkol Village, Semarang Regency aims to determine the function of Nadrak Dance. Nadrak dance is one of the folk dances in the Rukun Santosa Association which is danced in groups. The main problem of this research is the function of the Nadrak Dance. This research uses function theory. The theory of function was expressed by Bastomi. This research is qualitative. The data were collected through observation, interviews, and literature study. The results of this study the authors reveal the form and function of the Nadrak Dance. Form includes elements of motion, rhythm, expression or feeling, costumes, stage, and dancers. Nadrak Dance functions as a sacred art (religious interests) and secular art (a means of communication, education, and recreation).